Gender, presidencies, and Prime Ministerships in Europe: are women gaining ground? - Jalalzai, Farida (2014)
To what extent have women made progress in attaining presidential and prime ministerial positions in Europe? We might expect women in this region to have made significant strides in executive office holding, given the more favorable political, cultural, and social conditions women face. At the same time, Europe is not monolithic. The diversity within one large region allows not only for an assessment of the conditions best facilitating women's executive incorporation but also the ability to scrutinize the degree to which they exercise more substantial powers. While Europe boasts the greatest numbers of women executives to date, women face many limits in the type of positions they occupy and powers afforded their offices, although important exceptions surface. Statistically, women's success relates to dual executive structures. Likewise critical is the pipeline from which future leaders are recruited. Prospects for women leaders in Eastern Europe appear less auspicious than for their West European counterparts, further demonstrating women's uneven advances. Numbers, pathways, and political clout shape women's advancement in this historically male preserve, resulting in mixed progress overall. - Reproduced.
Keywords: Presidents; Prime ministers; Women in politics